Improved clinical outcome after acute basilar artery occlusion since the introduction of endovascular thrombectomy devices - Nagel, Simon; Kellert, Lars; Möhlenbruch, Markus Alfred; Bösel, Julian; Rohde, Stefan; Ringleb, Peter A. (Cerebrovascular diseases, 2013)
Thrombectomy devices are increasingly used for intra-arterial recanalization therapy in stroke. We analyzed whether the use of these devices modified the outcome of patients with acute basilar occlusion (BAO) at our institution. Between 1998 and 2012, one hundred forty-seven consecutive patients with acute BAO received recanalization therapy. In July 2009, for the first time, a thrombectomy device was used and hence the cohort was split into two chronological groups: BAO-1 (before July 2009) and BAO-2 (after July 2009). All patients were treated at a dedicated neurological ICU following institutional standard operating procedures. A good clinical outcome was defined as a modified Rankin scale score of 0-2 after 3 months. Univariate and multivariate analyses were applied using outcome parameters as dependent variables and baseline variables with a significant p value in univariate tests as independent variables. Results: One hundred eleven patients (BAO-1) were treated before and 36 were treated after July 2009 (BAO-2). Patients in the BAO-1 and BAO-2 groups had similar neurological deficits on admission as expressed by the Glasgow Coma Scale (BAO-1: median 4, IQR 5, vs. BAO-2: median 4.5, IQR 8, p = 0.41) and the proportion of patients who were presented intubated and ventilated was similar in both groups as well (49.5 vs. 47.7%, p = 0.85). Bridging concepts with intravenous recombinant tissue plasminogen activator (rtPA) were applied in 18.9% (BAO-1) versus 63.9% (BAO-2, p < 0.001) of cases, whereas glycoprotein IIb/IIIa antagonists were used significantly more frequently in the BAO-1 cohort (57.7 vs. 33.3%, p = 0.034). Thrombectomies were performed in 20 patients (55.5%) of the BAO-2 group but in none of the BAO-1 cohort. Complete recanalization (TICI 3) was achieved in 45.1% (BAO-1) versus 66.7% (BAO-2, p = 0.062) of patients. A good clinical outcome was observed in 13.5% of the BAO-1 group and 30.6% of the BAO-2 cohort (p = 0.026); mortality was 57.7% in the earlier group and 36.1% in the later group (p = 0.034). The frequency of symptomatic intracranial hemorrhage was similar in both groups (8.1% BAO-1 vs. 2.8% BAO-2, p = 0.45). Treatment in the BAO-2 cohort was an independent predictor of good clinical outcome (OR 2.56; 95% CI 1.01-6.78) and mortality (OR 0.36; 95% CI 0.15-0.86) in an adjusted logistic regression model. Conclusion: Our results show improved outcomes in patients in the BAO-2 cohort. The treatment approach in this group was an independent predictor of both good outcome and mortality. Especially in patients with BAO - where endovascular treatment strategies are common clinical practice - bridging protocols with rtPA and modern thrombectomy devices should be used more frequently.